PROFIL PEMECAHAN MASALAH SOAL CERITA STATISTIKA DITINJAU DARI GAYA KOGNITIF SISWA KELAS VIII SMP NEGERI I BAMBALAMOTU - S., Sarkia; Murdiana, I Nyoman; M., Bakri (Universitas Tadulako, 2023)
This study aims to describe the profile of students' problem solving status based on cognitive style. This type of research is descriptive research using a qualitative approach. Determination of research subjects using the Group Embedded Figure Test (GEFT) test developed by Witkin (1973). The results of this research are. Data analysiswas carried out with data reduction stages, data prsentasions, and conclusions/verifikation stages: 1). Problem solving with Field Independent cognitive style is at the stage of understanding the problem the subject writes what is known and asked from the question and can also explain the problem in his own sentence, at the stage of designing problem solving the subject is able to determine the appropriate plan to solve the problem, at the stage of implementing the solution plan the subject of the problem can apply a predetermined plan to solve the problem and also get the correct answer, at the stage of re-examining the subject writes the final conclusion but does not re-examine the calculations made. 2). Problem solving with Field Dependent cognitive style is at the stage of understanding the subject can determine what is known and asked in the problem, and can explain in his own sentence even though it is not much different from the question sentence, at the planning stage the subject is able to determine the appropriate plan to solve the problem. the stage of implementing the plan the subject can apply the predetermined plan to solve the problem and also get answers, at the stage of re-examining the subject writes the final conclusion but does not re-examine the calculations made.